2007
DOI: 10.1177/105381510703000105
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of E-mail Feedback on the Verbal Behaviors of Pre-service Teachers

Abstract: baseline design across 3 student teachers. Results were similar to Experiment I. Student teachers' use of expansions displayed more variability than the practicum students. Implications for (a) the identification of effective practices for university supervisors, (b) the use of e-mail to communicate between supervisors and pre-service teachers, (c) future research on feedback, and (d) methods for conducting systematic replications are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
124
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(132 citation statements)
references
References 14 publications
7
124
1
Order By: Relevance
“…Given the preliminary success of this approach, it would make sense to replicate with teachers of similar backgrounds but with added supports to help teachers implement the strategies as consistently as possible. Although the provider offered written summaries at the end of each session, future studies could use graphical feedback more systematically (Barton & Wolery, 2007;Casey & McWilliam, 2008). Future work could also examine ways to include additional teacher input into intervention planning to make the process more collaborative.…”
Section: Future Directionsmentioning
confidence: 96%
See 1 more Smart Citation
“…Given the preliminary success of this approach, it would make sense to replicate with teachers of similar backgrounds but with added supports to help teachers implement the strategies as consistently as possible. Although the provider offered written summaries at the end of each session, future studies could use graphical feedback more systematically (Barton & Wolery, 2007;Casey & McWilliam, 2008). Future work could also examine ways to include additional teacher input into intervention planning to make the process more collaborative.…”
Section: Future Directionsmentioning
confidence: 96%
“…Research from multiple fields also highlights the importance of feedback on the adult's acquisition of new skills (Dunst & Trivette, 2009;Knowles, Holton, & Swanson, 2005;Reinke, Lewis-Palmer, & Martin, 2007;Reinke, Lewis-Palmer, & Merrell, 2008). When adults receive specific information regarding how they used a new skill, they are better able to integrate the feedback into future performances (Barton & Wolery, 2007;Casey & McWilliam, 2008). Performance-based feedback may include specific information about the adult's actions and behaviors when practicing a new skill and it may set up further opportunities for practice (Hattie & Timperley, 2007;Noell et al, 2005;Woods, Wilcox, Friedman, & Murch, 2011).…”
Section: A Situated Coaching Approach: Kidtalk Tactics Projectmentioning
confidence: 99%
“…As was emphasized in similar studies (Barton & Wolery, 2007;Cossairt, Hall, & Hopkins, 1973;Mesa et al, 2005;Sutherland, Wehby, & Copeland, 2000), the PF which was used in the teacher education positively changed the teachers' classroom management strategies. The effectiveness findings of this study showed that PF might be used in teacher education as a short-term, problemfocused, effective solution.…”
Section: Discussionmentioning
confidence: 80%
“…Preparation of the Intervention Program: In order to prepare the information material for use in this study, literature related to preventive classroommanagement strategies (Barton & Wolery, 2007;Casey & McWilliam, 2008;Colvin, Flannery, Suga, & Monegan, 2009;DiGennaro, Martens, & Kleinmann, 2007;Mesa et al, 2005;Reinke et al, 2008) were reviewed. The researcher made observations in the classrooms of the teachers using the PCMOF, and she performed interviews with the subjects.…”
Section: Implementation Pre-intervention Studiesmentioning
confidence: 99%
“…Coaching via performance feedback was identified as the method of ongoing support because it has demonstrated efficacy in a variety of fields within and outside of education (Alvero et al, 2001;Balcazar et al, 1985;Mortenson & Witt, 1998;Noell et al, 2000Noell et al, , 2005. More recent findings also support the use of performance feedback focused on the implementation of evidence-based practices in early childhood classroom contexts (Barton & Wolery, 2007;Cambray-Engstrom & Salisbury, 2010;Casey & McWilliam, 2008;Hemmeter et al, 2011;Manturana & Woods, 2012). Given previous work establishing that changing teacher practices generally requires more than isolated trainings or workshops (Showers, Joyce, & Bennett, 1987), performance feedback based on direct observation of implementation of the new practice is becoming a key component of professional development interventions intended to support teachers' high fidelity implementation of empirically supported practices.…”
Section: Discussionmentioning
confidence: 90%